Association between post-stroke psychological disorders, activity limitations and health-related quality of life in chronic stroke survivors in Benin - ATIGOSSOU, DIDIER COMLAN; Ouedraogo, Fatima; Henado, Aristide; ALAGNIDE, HOUNTONDJI ETIENNE; KPADONOU GODONOU, TOUSSAINT (My University, 2022)
Purpose: To evaluate the association between depression/anxiety and activity limitations and health- related quality of life (HRQoL) in chronic stroke survivors in Benin. Materials and methods: One hundred and seventy-six chronic stroke survivors (113 males; mean age (±SD): 56.5 (±10.5) years old) were included. We used the Barthel index (BI) to assess activity limitations. Participants were screened for depression and anxiety symptoms using Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HARS). Euroqol-5 Dimensions-3 Levels (EQ-5D-3L) including a Visual Analog Scale (EQ-VAS) was used to assess HRQoL. Multivariate linear regressions were performed to determine the impact of psychological disorders on activity limitations and HRQoL. Results: Depression (b¼–0.54; p<0.0001) and anxiety (b¼–0.35; p<0.0001) were negatively associated with activity limitations (R2¼0.60). Similar patterns of association were observed with HRQoL (b–0.28; p<0.0001; R2 0.40). Inversely, occupational status showed positive association with EQ-5D-3L summary index scores (b¼0.21; p¼0.015). Conclusions: Depression and anxiety had a negative impact on activity limitations and HRQoL in Beninese chronic stroke survivors. This call for action to integrate psychological interventions as part of rehabilitation programs in low and middle-income countries.
Keywords: Stroke survivors; activity limitations; depression; anxiety; health-related quality of life